BASIC CRITERIA OF QUALITY AND EFFICIENCY PROJECTS SAVING - , Г. Е. (Municipal economy of cities. Series: «Economy science», 2013)
The problem of assessing the quality and effectiveness of resource projects in enterprises of housing and communal services, the main evaluation criteria.